Pharmacological chaperone search for arylsulfatase a enzyme (ARSA) and characterization of two novel mutations - Eren, Ayşe. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
Arylsulfatase A (ARSA) is an important lysosomal enzyme whose deficiency due to misfolding or oligomerization loss causes a lethal neurodegenerative disease called Metachromatic Leukodystrophy Disease (MLD). This is an autosomal, recessively inherited and fatal disease causing loss of motor function and intellectual skills mostly in infants and children. Expensive treatments such as enzyme replacement therapy can be used to increase ARSA levels, but any drug candidate has not been determined yet, thus there is an urgent need for the discovery of a drug candidate for ARSA. Pharmacological chaperones (PC) have been considered to be drug candidates for neurodegenerative diseases. The aim of this study was to understand the effects of two disease causing mutations and to find a novel PC candidate for two novel ARSA mutations: W318C and E307K+T391S. Molecular dynamics (MD) simulations were performed on wild type (WT) and mutant ARSA monomers and dimers at both acidic, and neutral pH to understand the effects of the mutations on the enzyme. The analyses of the MD simulations showed that E307K+T391S might be causing a change in the association angle at the dimer interface, while W318C may be affecting folding. Docking calculations and pharmacophore model search were performed on the monomer forms using various molecule sets and natural ligands. Six of these molecules were selected for further MD simulations. The results of the apo forms and ligand bound forms were compared in terms of enzyme dynamics and structural changes on the protein. Finally, two molecules (R_5 and ZINC90709065
Keywords: Arylsulfatases.